Floral volatile signatures as cultivar-specific metabolic fingerprints in mango (Mangifera indica L.) - Abeer Ali; Nimisha Sharma; Ansheef Ali; Haritha Bollinedi; Hatkari Vittal; Vishal Kumar; Akshay; Mukesh Shivran; Damini Singh; Jai Prakash; R.M. Sharma; A.K. Dubey (Biochemical Systematics and Ecology, 2026)

Changes in the spatial connection and synchronization of extreme rainfall events in recent decades over the Ganga and Yamuna River Basins of India - Ripunjay Pandey; Pragati Prajapati; Ashish Kumar Meena; Akshay Singhal; Sanjeev Kumar Jha; Kundan Kandhway (Atmospheric Research, 2026)

Photoacoustic Visualization of 7,12-Dimethylbenz[a]anthracene-Induced Breast Tumor by Multi-dosing of Tamoxifen-Loaded Albumin Nanoparticles - Akshay Kale; Vaishali; Nidhi Verma; Aseem Setia; Nandini Vinodrao Randhave; Komal Rani; Vikas Kumar; Madaswamy S. Muthu (Journal of Pharmaceutical Innovation, 2026)

Quality-by-Design Steered Development and Validation of Analytical Method for the Estimation of Etodolac: Integration of Monte Carlo Simulations and Green Analytical Principles - Akshay Kumar; Mohit Kumar; Pallavi Bassi; Balraj Saini; Narinderpal Kaur; Chander Parkash Dora; Gopal Thakur (Journal of Pharmaceutical Innovation, 2026)

Application of chitosan-based nanomatrix enriched with Melaleuca alternifolia essential oil against the growth of storage fungi and aflatoxin B1 contamination in maize seeds - Vivekanand; Akshay Kumar; Vishal Gupta; Tanya Singh Raghuvanshi; Bhanu Prakash (Brazilian Journal of Microbiology, 2026)

Ultraviolet-C treatment of spices and herbs: A critical review on microbial safety and quality retention - Sandeep Sarkar; Akshay H. Dasalkar; Sudheer Kumar Yannam (Food Research International, 2026)

Epigenetic Regulation of Stress Tolerance and Fruit Quality in Fruit Crops - T. E. Tejas; Akshay Mehta; Satpal Baloda; Sarita Devi; Vikas Kumar Sharma; Aman Kumar (Applied Fruit Science, 2026)

In vitro evaluation of venom extracts of Sphecid wasps against phytopathogens of horticultural crops and mass spectrometric profiling of venom peptide components - C. Manasa; J. Jayappa; Jayashree Ugalat; Akshay Kumar; B. N. Maruthi Prasad; G. K. Ramegowda; T. B. Manjunatha Reddy; L. T. Nikita (International Journal of Tropical Insect Science, 2026)

Toward non-transgenic hybrid microalgal platforms for astaxanthin production under CO2-rich conditions: A conceptual roadmap - Akshay Kumar; Reeta Rani Singhania; Vanshika Nimker; Yamini Sumathi; Cheng-Di Dong; Anil Kumar Patel (Algal Research, 2026)

Enhancing urban flood management for ungauged watersheds through adaptive mesh refinement and equation-based flow dynamics - Akshay Kumar; Nikhil Reddappa; Srinivas Rallapalli; Saumitra Rai; Rajiv Gupta (Hydrological Sciences Journal, 2026)

Comparative Plastome Analysis of Citrus sinesis with other Fruit Crops and cpSSR Development and Validation in Citrus Hybrids - Nimisha Sharma; Narendra Singh; Raushan Kumar; Mukesh Shivran; Akshay; Neha Sharma; Dhrumeshkumar Chavda; Lal Chand; A. K. Dubey; R. M. Sharma; S. K. Singh; Gyan Prakash Mishra; et al. (Tropical Plant Biology, 2026)

Global Water Scarcity: Understanding Challenges, Causes, and Mitigation Measures - Akshay Kumar Singh; Soham Mishra; Aman Kumar Singh; Mallikharjuna Prasad Polavarapu; Amit K. Singh; Sughosh Madhav; Ajai Singh; Manoj Kumar; Sushil Kumar Shukla (Water Conservation Science and Engineering, 2026)

Comprehensive study on phytochemical constituents and bioactive potential of aerial part extracts of Strobilanthes attenuata: an underexplored medicinal plant - Anantpreet Kaur; Akshay Kumar; Harpreet Walia; Samriti Khosla (Plant Biosystems, 2026)

Whole genome analysis reveals chromosomal and plasmid-mediated convergence of drug resistance in Klebsiella pneumoniae isolates - Dhinakaran Irusan; Akshay Sadanand Dangari; Varsha Prakash Shetty; Iddya Karunasagar; Vijaya Kumar Deekshit; Anusha Karunasagar (Antonie van Leeuwenhoek, 2026)

Green nanomaterials from renewable Biomass: Sustainable Synthesis, environmental Applications, and Life-Cycle implications - Dilpreet Singh; Akshay Kumar; Pooja A. Chawla; Viney Chawla (Environmental Nanotechnology, Monitoring & Management, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Hormone-optimized hypocotyl–epicotyl–cotyledonary tri-complex explant system enables efficient soybean transformation with reduced genotype dependence - J. Sushmitha; Durgeshwari Prabhakar Gadpayale; Navita Bansal; Ranjeet R. Kumar; G. Rama Prashat; Shivani Nagar; Soham Ray; Ashish Marathe; R. Dinesh Kumar; Akshay Talukdar; Giriraj Kumawat; Viswanathan Chinnusamy; et al. (Plant Cell Reports, 2026)

Rootstock-Mediated Nutrient Dynamics in Leaves, Buds and Panicles of Regular- and Alternate-Bearing Mango Cultivars - Hatkari Vittal; Nimisha Sharma; Akshay; R. M. Sharma; Nripendra Vikram Singh; Narendra Singh; Mahesh Chand Meena; Tirunagari Rupesh; Abeer Ali; Vishal Kumar; Anil Kumar Dubey; Gyan P. Mishra; et al. (Journal of Plant Growth Regulation, 2026)

AQbD enabled analytical method development and validation for simultaneous estimation of Asiaticoside (AC) and Chlorhexidine (CHX) in nanostructured lipid carriers - Akshay Kumar; Abhishek Chauhan; Devesh Kumar; Arpan Kumar Tripathi; Ankit Awasthi; Thakur Gurjeet Singh; Suresh Babu Kondaveeti; Mohit Kumar (Journal of Pharmaceutical Innovation, 2026)

Critical habitats for sharks and rays in Asia remain largely unprotected - Adriana Gonzalez-Pestana; Peter M. Kyne; Emiliano García-Rodríguez; Ryan Charles; Vanessa Bettcher Brito; Asia O. Armstrong; Amanda Batlle-Morera; Marta D. Palacios; Christoph A. Rohner; Giuseppe Notarbartolo di Sciara; Jo Marie V. Acebes; Serena Adam; et al. (Biodiversity and Conservation, 2026)
The Asia region harbors exceptional chondrichthyan (shark, ray, and chimaera) diversity but faces intense fishing pressure. The Important Shark and Ray Areas (ISRA) process provides a collaborative, evidence-based framework to identify critical habitats and inform spatial management. We assessed ISRAs across the Bay of Bengal, Southeast Asia, and the Northwest Pacific to characterize their extent, ecological significance, and conservation relevance. We delineated 122 ISRAs spanning ~ 1 million km 2 (~ 3% of the region) across 12 jurisdictions and international waters, encompassing habitats for 121 species (~ 30% of Asia’s chondrichthyans), 76% of which are threatened. Depleted taxa (e.g., giant guitarfishes, Glaucostegidae) were represented, but charismatic megafauna (e.g., Whale Shark Rhincodon typus ) were overrepresented. In contrast, deepwater and freshwater species were underrepresented. Reproductive Areas were the most common ISRA sub-criterion applied (52% of ISRAs), largely in nearshore zones, while areas for range-restricted species were less frequently (18%) identified. Twelve ISRAs overlapped with biodiversity hotspots, including seven in areas of high overall chondrichthyan species richness and five in areas of high range-restricted species richness. Citizen science was the predominant research method used to delineate ISRAs, while fisheries data were underused despite the region’s major fisheries footprint. Geographic coverage was uneven: Indonesia held the most ISRAs (n = 40; 71.7% of ISRA coverage) while eight jurisdictions (e.g., Viet Nam, China, Republic of Korea) lacked ISRAs due to data gaps. Protection shortfalls are stark: MPAs cover

Mitochondrial Dysfunction Predisposes Radioresistant Insect Cells to Ionizing Radiation by Impairing DNA Repair - Shubhankar Suman; Akshay Pandey; Rakesh Kumar Seth; Sudhir chandna (Cell Biochemistry and Biophysics, 2026)

Modeling spinal cord injury: bridging in vitro systems and in vivo complexity - Rutuja Satvase; Saumya Jaiswal; Manjeet Chopra; Hemant Kumar; Akshay Srivastava (In vitro models, 2026)

Thermo-Sensitive Polymeric Networks for Next-Generation Wound Management: A Review - Akshay Kumar; Prachee Nirmale; Suresh Babu Kondaveeti; Arpan Kumar Tripathi; Jailani Shiekmydeen; Sagar Nanaso Salunkhe; Gurjeet Singh Thakur; Mohit Kumar (AAPS PharmSciTech, 2026)

Environmental implications of coal mining and its sustainable mitigation by Phytoremediation: A comprehensive review - Akshay Kumar Singh; Jatin Kumar Choudhary; Mallikharjuna Prasad Polavarapu; Sushil Kumar Shukla; Ajai Singh; Manoj Kumar (Environmental Monitoring and Assessment, 2026)

Retraction notice to “Levothyroxine synthesis impurities are neither mutagenic nor genotoxic: Insilico, Ames test and micronucleus test studies” [Mutat. Res. - Genet. Toxicol. Environ. Mutagenesis 898 (2024) 503796] - Rajesh Rane; Akshay Prabhune; Dileep Kumar; Ajay Kumar; Madhur Sewlikar; Mugdha Suryawanshi; Bharat Satpute; Bapu Gawade; Sachin Sakat (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2026)

Rapid strengthening of tropical cyclones and their characteristics across the decades over the North Indian ocean - Akshay Kumar Sagar; Priyankar Kumar; Akshat Dimri (Ocean Dynamics, 2026)

Microneedle-Assisted Delivery of Biologics: From Large Molecules to Cancer Vaccines - Salma Younas; Mohit Kumar; Ramsha Khalid; Kirthana Gopal; Akshay Kumar; Pornanong Aramwit; Syed Mahmood (AAPS PharmSciTech, 2026)

Visnagin attenuates thioacetamide-induced kidney damage through suppression of renal injury marker, oxidative stress, inflammation, apoptosis, and TGF-β-mediated renal fibrosis - Akshay Amruta Navghare; Sonu Rajput; Poonam Yadav; Sumeet Kumar Singh; Yogender Goswami; Jasvinder Singh Bhatti; Umashanker Navik (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Upcycling of waste Geranium leaves into biochar for soil amendment - Chalasani Danteswari; Pullabhotla V.S.R.N. Sarma; Akshay Rao; Dharani Kumar Chennamsetty; Ravikiran Nowduru; Appa Rao Podile; Venkata Satya Siva Srikanth Vadali (Biomass and Bioenergy, 2026)

Optimizing GEDI Footprint Selection for Forest Canopy Height Estimation in the Western Himalaya Using Multi-sensor Data - Akshay Paygude; Hina Pande; Poonam Seth Tiwari; Praveen Kumar Varma; Manoj Kumar (Journal of the Indian Society of Remote Sensing, 2026)

Residential indoor and outdoor exposure to VOCs and NO2: insights from a multi-city pilot study in India - Prince Vijay; Akshay Kumar; Shreya Dubey; Rajdeep Singh; Vinayak Sahota; Sonali Borse; Harish C. Phuleria (Environmental Geochemistry and Health, 2026)

Unified Phenological Characterization of Fruit Crops Using the Extended BBCH Scale - Aman Kumar; Akshay Mehta; Vikas Kumar Sharma; Sushil Sharma; Pravin Kumar Sharma; Prince (Applied Fruit Science, 2026)

Smart Stings of Nature: Harnessing Microneedles Assisted Targeted Phytoconstituent Delivery for Dermatological Disorders - Akshay Kumar; Suresh Babu Kondaveeti; Arpan Kumar Tripathi; Mohit Agrawal; Thakur Gurjeet Singh; Devesh Kumar; Mohit Kumar (AAPS PharmSciTech, 2026)

Signaling Pathways Triggering Therapeutical Potential of Marine-Derived Polysaccharides in Alzheimer’s Disease: A Recent Review - Devesh Kumar; Suresh Babu Kondaveeti; Mohit Agrawal; Akshay Kumar; Ankit Awasthi; Syed Mahmood; Thakur Gurjeet Singh; Mohit Kumar (Molecular Neurobiology, 2026)

Signalling pathways triggering therapeutic marine algae-derived natural polysaccharides for effective wound healing: A recent review - Suresh Babu Kondaveeti; Arpan Kumar Tripathi; Devesh Kumar; Akshay Kumar; Thakur Gurjeet Singh; Syed Mahmood; Kajal Ghosal; Ankit Awasthi; Mohit Kumar (Carbohydrate Polymers, 2025)

Retrieval of satellite-derived black carbon concentration and mitigation approaches for Karnataka, India - Narayan Kayet; Likitha M P; Akshay Kumar V G; Geeta Hegde; Tejaswini Eregowda; Chandana M C (Atmospheric Environment, 2025)

Assessment of heavy metal contamination in roadside soil and its uptake by selected tree species in urban and semi-urban regions - Akshay Kumar Singh; Jatin Kumar Choudhary; Sushil Kumar Shukla (Urban Ecosystems, 2025)

Psychobiotics and the gut-brain axis: advances in metabolite quantification and their implications for mental health - Vincent Owusu Kyei-Baffour; Akshay Kumar Vijaya; Aurelijus Burokas; Eric Banan-Mwine Daliri (Critical Reviews in Food Science and Nutrition, 2025)

First report of Alternaria tenuissima causing leaf blight disease on Madhuca longifolia (Mahua) seedlings in India - K. Darshan; Charishma Krishnappa; Fatima Shirin; S.N. Mishra; Sourabh Dubey; Dolly Parte; H.M. Akshay Kumar (Physiological and Molecular Plant Pathology, 2025)

Application of hybrid gradient boosting machine to reliably predict rate of penetration - JiaNing Zhang; Farag M.A. Altalbawy; Tarak Vora; R. Manjunatha; Debasish Shit; Nargiza Kamolova; Akshay Kumar; Atreyi Pramanik; Ajay Sharma; Tamam Ali Abd Ulabbas Abedi; Ahmad Abumalek; Mohammad Mahtab Alam; et al. (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Impact of primary aerosol particles on size specific oxidative potential and its relationship with air quality and hazard index - Atar Singh Pipal; Sachin D. Ghude; P.G. Satsangi; Milindkumar Yashvant Bhatkar; Akshay Kale; Sandip S. Nivdange; M. Nageswar Rao; Arkabanee Mukherjee; Akash S. Vispute; Hardeep Sharma; Vikash Kumar; Prasanna Lonkar; et al. (Atmospheric Environment, 2025)

Advances in Pharmaceutical Cocrystals and Nano-Cocrystals: Strategies for Enhancing Solubility and Translating to Clinical Use - Roshan P. Rao; Jawahar Natarajan; Samanwita Khanra; Jey Kumar Pachiyappan; Imrankhan Nizam; Akshay Muralidhara; Jubie Selvaraj; S. Selvamuthukumar (AAPS PharmSciTech, 2025)

A Bayesian reliability methodology for rock structures considering uncertainties in random field characteristics with limited data of rock properties - Akshay Kumar; Gaurav Tiwari (International Journal of Rock Mechanics and Mining Sciences, 2025)

Plants Response to Different Abiotic Stresses - Sami Jan; M. Ashraf Bhat; Akshay Kumar; M. Altaf Wani; Farooq Ahmad Bhat; Raihana H. Kanth; A. B. Shikari; Haleema Bano; Tabasum Manzoor; Heena Altaf; Noor-ul-Ain; Zafir Ahmad Naik (Journal of Crop Health, 2025)

Decoding Phytophthora meadii (McRae): the first genomic insights into the arecanut fruit rot pathogen - M. K. Rajesh; V. H. Prathibha; Bobby Paul; Roli Budhwar; Rohit Shukla; Akshay Dinesh; K. P. Gangaraj; R. Thava Prakasa Pandian; Jasmin Habeeb; B. J. Nirmal Kumar; M. Chaithra (Journal of Plant Pathology, 2025)

Black carbon emissions from road transport in Karnataka, India: High-resolution inventory and mitigation strategies - Narayan Kayet; Likitha M P; Geeta Hegde; Akshay Kumar V Ganeshker; Tejaswini Eregowda (Science of The Total Environment, 2025)

Analysis of urban flood vulnerability at the sub-city administrative unit level in Mumbai: A comparison over two time periods - Pragati Prajapati; Akshay Singhal; Sanjeev Kumar Jha (Urban Climate, 2025)

Development and characterization of carrageenan-based antibacterial films incorporated with natural melanin pigment from niger seed hulls (Guizotia abyssinica) and their efficacy to enhance the shelf-life of strawberries - B.T. Sunil Kumar; Jeevan Prasad Reddy; V. Vanajakshi; Akshay H. Dasalkar; Sudheer Kumar Yannam; Umesh H. Hebbar; Sridevi Annapurna Singh (Food Control, 2025)

Fish diversity and community structure during open and closed mouth states in Poovar—a small temporarily closed tropical Indian estuary - Sreekanth Giri Bhavan; Keerthana Prakash Sini; Akshay A. Kumar; Soorya Gopan; Arunima Biju Kumar; Shamini Mettincy Shaji; Kiranya Bella (Marine Biodiversity, 2025)

Integrating Quality by Design (QbD) in Phytosomal Drug Delivery: A New Era in Precision Phytotherapy - Sumant Kumar; Omar Awad Alsaidan; Sami I. Alzarea; Akshay Kumar; Suresh Babu Kondaveeti; Diksha Sharma; Mohit Kumar; Devesh Kumar (AAPS PharmSciTech, 2025)

Climate Response of the Seven Homogeneous Monsoon Rainfall Regions of India Using the SOLAR Geoengineering Simulation Datasets - Akshay Kumar Sagar; Arun Chakraborty (Aerosol Science and Engineering, 2025)

Synergistic effect of molybdenum and Rhizobium on growth and yield of vegetable cowpea (Vigna unguiculata (L.) Walp.) - Monu Kumari; Nitin B. Patel; Kapil Dev Ameta; Akshay Kumar Yogi; Harshit Kumar; Ayushi Jain (Vegetos, 2025)

Study of accumulated cyclone energy and associated drivers affecting tropical cyclone activities over the North Indian Ocean during the pre- and post monsoon season - Akshay Kumar Sagar; Arun Chakraborty; Swadhin Kumar Behera; Abhishek Kumar (Natural Hazards, 2025)

ZIF-based hybrid magnetic nanocomposites for the removal of organic pollutants - Gaurav Sharma; Akshay Verma; Tongtong Wang; Amit Kumar; Pooja Dhiman; Genene Tessema Mola; Jinhu Zhi (Journal of Water Process Engineering, 2025)

Micro-macro–scale flood modeling in ungauged channels: Rain-on-grid approach for improving prediction accuracy with varied resolution datasets - Akshay Kumar; Sripali Biswas; Srinivas Rallapalli; Pratik Shashwat; Selva Balaji; Rajiv Gupta (Journal of Hydrology, 2025)

Chemical and toxicological characteristics of fine particles from festive fireworks in urban residential communities - Shreya Dubey; Vinayak Sahota; Akshay Kumar; Nidhi Prajapati; Vijaya Laxmi; Balram Dangi; Harish C. Phuleria (Atmospheric Environment, 2025)

Biomedical waste management: navigating the challenges to achieve the promise of sustainable development goal 3 - Varsha Prakash Shetty; Sadanand Dangari Akshay; Barani Devi Thilai; Vijaya Kumar Deekshit (Waste Disposal & Sustainable Energy, 2025)

Prediction of Air Quality Index (AQI) using machine learning-based tree models—a case study of Gurugram City, India - Akshay Kumar; Parveen Sihag; Karan Singh; Fatemeh Esmaeilbeiki; Balraj Singh; Hari Om (Theoretical and Applied Climatology, 2025)

Sodicity tolerance in Jamun (Syzygium cumini L. Skeels) genotypes based upon growth and physiological traits - Rajkumar; Ashwani Kumar; Anshuman Singh; Nirmal Singh; Akshay Kumar; Pratibha Poonia; Antim Kundu (Plant Physiology Reports, 2025)

Integrated omics analysis of rice gene expression profiles and microRNAs identifies crucial target genes for nitrogen use efficiency - Kalyani M. Barbadikar; Krishna Kant Talapanti; Sonali Bej; Suman Karre; Harish Kothandaraman; S. Malathi; Raghuveer Rao Puskur; Satendra Kumar Mangrauthia; Subrahmanyam Desiraju; S. R. Voleti; Akshay Sureshrao Sakhare; M. S. Anantha; et al. (Plant Physiology Reports, 2025)

Evaluating Machine Learning Classifiers for IRS High Resolution Satellite Images Using Object-Based and Pixel-Based Classification Techniques - Akshay Kumar; Gaurav Kumar; Deshbhushan Savindra Patil; Rajiv Gupta (Journal of the Indian Society of Remote Sensing, 2025)

Enhancing virus resistance through pre-breeding and crossability experiments in okra (Abelmoschus esculentus (L.) Moench) - S. Santhiya; Ramesh Kumar Yadav; Suman Lata; Bhoopal Singh Tomar; Akshay Talukdar; Avinash Tomer; C. Vaishali; P. Prabhu; Koku Tara (Genetic Resources and Crop Evolution, 2025)

Effect of UV-C LEDs and heat treatments on microbial safety, chemical and sensory properties of sweet lime juice - Akshay H. Dasalkar; Anisha Biswas; Sachin R. Chaudhari; Sudheer Kumar Yannam (Food Chemistry, 2025)

Carboplatin Co-loaded 5-Fluorouracil Nanoparticles Conjugated with Trastuzumab for Targeted Therapy in HER2+ Heterogeneity Breast Cancer - Akshay Kumar Lunawat; Debanjan Mukherjee; Riya Shivgotra; Sarjana Raikwar; Ankit Awasthi; Amrinder Singh; Shamsher Singh; Shivani Chandel; Subheet Kumar Jain; Shubham Thakur (AAPS PharmSciTech, 2025)

Geospatial mapping and cluster analysis of antibiotic-resistant Escherichia coli in drinking water of semi-arid areas - Srishti Srivastava; Akshay Kumar; Rajiv Gupta; Abdul Malik (Environmental Monitoring and Assessment, 2025)

Assessing the Combined Toxicity of Silver and Copper Nanoparticles in Rainbow Trout (Oncorhynchus mykiss) Fingerlings - Saba Khursheed Khan; Joydeep Dutta; Mohd Ashraf Rather; Ishtiyaq Ahmad; Junaid Nazir; Showkat Shah; Suhas Ballal; Akshay Garg; Faisal Imam; Abhinav Kumar (Biological Trace Element Research, 2025)

Foam-Based Drug Delivery Systems for Skin Disorders: A Comprehensive Review - Syrsulu Myrzagulova; Zhexenova Azhar N; Mohit Kumar; Devesh Kumar; Akshay Kumar (AAPS PharmSciTech, 2025)

Advances in photocatalytic hydrogen production with ZnO/ZnS-Based nanostructured materials - Parul Rana; Vatika Soni; Rohit Kumar; Sonu; Akshay Chawla; Aftab Aslam Parwaz Khan; Pardeep Singh; Sourbh Thakur; Pankaj Raizada; Khalid A. Alzahrani (Fuel, 2025)

Evaluating the role of tree flora in air pollution mitigation and heavy metals accumulation near brick kilns - Akshay Kumar Singh; Subhalaxmi Behera; Jatin Kumar Choudhary; Sushil Kumar Shukla (Atmospheric Pollution Research, 2025)

Exploration of Anomuran Crabs from the Intertidal zone of Kadmat and Amini Islands of the Lakshadweep Archipelago, India - Naseem N. M.; Jayalakshmi K. J; Davood Nihal; Akshay A. Kumar (Thalassas: An International Journal of Marine Sciences, 2025)

Dual-nutrient stress tolerance in wheat is regulated by nitrogen and phosphorus uptake, assimilation, reutilization, and differential expression of candidate genes - Renu Pandey; Sandeep Sharma; Ankita Mishra; Akshay Sureshrao Sakhare; Surendra Kumar Meena; Krishnapriya Vengavasi (Plant and Soil, 2025)

Geological and Cultural Heritage of Lithic Artefacts Unearthed from Fort Kochi, Southern India - R. T. Ratheesh-Kumar; B. Uthara; V. S. Duniya Raj; B. Devati; P. B. Akshay (Geoheritage, 2025)

Agroecosystem contamination with heavy metals due to road transportation: A global threat to safe food security - Akshay Kumar Singh; Jatin Kumar Choudhary; Sushil Kumar Shukla; Kuldeep Bauddh; Gavendra Pandey; Sughosh Madhav; Ajai Singh; Manoj Kumar (Process Safety and Environmental Protection, 2025)

An Imprecise Hybrid Reliability Methodology for Rock Structures Considering Spatial Variations of Inputs with Mixed Uncertainties: Theory and Application - Surabhi Maurya; Akshay Kumar; Gaurav Tiwari (Computers and Geotechnics, 2025)

CRISPR/Cas12a mediated rapid and efficient detection of Tomato Leaf Curl Karnataka Virus without amplification - Thalooru Shashikala; Dhawane Yogi; Kumar Akshay; Karuppannasamy Ashok; Somakalahalli Narasimhappa Nagesha; Maligeppagol Manamohan; Girish Kumar Jha; Ramasamy Asokan (Biocatalysis and Agricultural Biotechnology, 2025)

CRISPR-Cas technology: an emerging opportunity for precise identification of diseases in plants - C. Shanmugaraj; H. M. Akshay Kumar; V. Jaiganesh; M. K. Biswas; R. Gangaraj (Journal of Plant Diseases and Protection, 2025)

Amelioration of breast cancer therapies through normalization of tumor vessels and microenvironment: paradigm shift to improve drug perfusion and nanocarrier permeation - Paras Famta; Saurabh Shah; Ganesh Vambhurkar; Giriraj Pandey; Deepkumar Bagasariya; Kondasingh Charan Kumar; Sajja Bhanu Prasad; Akshay Shinde; Suraj Wagh; Dadi A. Srinivasarao; Rahul Kumar; Dharmendra Kumar Khatri; et al. (Drug Delivery and Translational Research, 2025)

Investigating role of corn stover biochar supplementation on continuous pilot scale anaerobic digestion: Performance and microbial community dynamics - Sachin Krushna Bhujbal; Preeti; Akshay Joshi; Pooja Ghosh; Virendra Kumar Vijay (Bioresource Technology, 2025)

Pressure Drop and Interfacial Heat Transfer Coefficient Formulation for Packed Bed Systems with Cylindrical Capsules - Akshay Kumar; Pratyush Kumar; Sandip K. Saha (Transport in Porous Media, 2025)

Quality by design empowered preparation of itraconazole albumin nanoparticles for prostate cancer - Saurabh Shah; Paras Famta; Anamika Sharma; Rahul Kumar; Giriraj Pandey; Ganesh Vambhurkar; Dadi A. Srinivasarao; Akshay Shinde; Sajja Bhanu Prasad; Amit Asthana; Saurabh Srivastava (Drug Delivery and Translational Research, 2025)

Genome-wide association study on root traits under non-stress and osmotic stress conditions to improve drought tolerance in rice (Oryza sativa Lin.) - Akshay Sureshrao Sakhare; Sudhir Kumar; Ranjith K. Ellur; G. D. Prahalada; Suneetha Kota; Ranjeet Ranjan Kumar; Soham Ray; Baidya Nath Mandal; Viswanathan Chinnusamy (Acta Physiologiae Plantarum, 2025)

Spatially explicit simulation and forecasting of urban growth using weights of evidence based cellular automata model in a millennium city of India - Pankaj Kumar Yadav; Varun Narayan Mishra; Maya Kumari; Akshay Kumar; Pradeep Kumar; Rajeev Bhatla (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Role of important physiological traits and development of heat tolerance index in a large set of diverse cucumber germplasm - Dhananjay A. Hongal; A. D. Munshi; Akshay Talukdar; Anjan Das; N. Pradeepkumara; M. Karthik Kumar; Jyoti Kumari; Viswanathan Chinnusamy; J. K. Ranjan; T. K. Behera; S. S. Dey (Acta Physiologiae Plantarum, 2024)

Development of 1 ×1 km gridded emission inventory for air quality assessment and mitigation strategies from open biomass burning in Karnataka, India - Narayan Kayet; Tejaswini Eregowda; Likitha M P; Akshay Kumar V Ganeshker; Geeta Hegde (Urban Climate, 2024)

Can pyrolysis handle biomedical wastes?: Assessing the potential of various biomedical waste treatment technologies in tackling pandemics - Akshay Srivastava; Anita Sharma; Manoj Kumar Jena; Arun K. Vuppaladadiyam; Febelyn Reguyal; Jyeshtharaj Joshi; Abhishek Sharma; Kalpit Shah; Akhilendra Gupta; Bridgid Lai Fui Chin; Agus Saptoro; Ajit K. Sarmah (Science of The Total Environment, 2024)

A top-down spatial scenario approach for identifying the locations of rainwater harvesting sites in an urban region - Gaurav Kumar; Deshbhushan Patil; Akshay Kumar; Rajiv Gupta (Environmental Science and Pollution Research, 2024)

Reliability analysis of deep tunnels in spatially varying brittle rocks using interval and random field modelling - Akshay Kumar; Surabhi Maurya; Gaurav Tiwari (International Journal of Rock Mechanics and Mining Sciences, 2024)

Impact of UV-C treatment on the inactivation of microbes and amino acid composition in cow milk and buffalo milk: A comparative study - Akshay H. Dasalkar; Raj Kumar Maguluri; Salony Raghunath Vaishnav; Sridevi Annapurna Singh; Sudheer Kumar Yannam (International Dairy Journal, 2024)

Modified speed breeding approach reduced breeding cycle to less than half in vegetable soybean [Glycine max (L.) Merr.] - Meniari Taku; Manisha Saini; Rahul Kumar; Pulak Debbarma; Nenavath Krishna Kumar Rathod; Reshma Onteddu; Deepshikha Sharma; Renu Pandey; Kishore Gaikwad; S. K. Lal; Akshay Talukdar (Physiology and Molecular Biology of Plants, 2024)

RETRACTED: Levothyroxine synthesis impurities are neither mutagenic nor genotoxic: Insilico, Ames test and micronucleus test studies - Rajesh Rane; Akshay Prabhune; Dileep Kumar; Ajay Kumar; Madhur Sewlikar; Mugdha Suryawanshi; Bharat Satpute; Bapu Gawade; Sachin Sakat (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2024)

Recent advances in synthesis methods and surface structure manipulating strategies of copper selenide (CuSe) nanoparticles for photocatalytic environmental and energy applications - Akshay Chawla; Anita Sudhaik; Sonu; Rohit Kumar; Pankaj Raizada; Aftab Aslam Parwaz Khan; Tansir Ahamad; Van-Huy Nguyen; Rangabhashiyam Selvasembian; Ajeet Kaushik; Pardeep Singh (Journal of Environmental Chemical Engineering, 2024)

Nanofabrication of citronellal with chitosan biopolymer to boost its efficacy against aflatoxin B1 and Aspergillus flavus mediated biodeterioration of active ingredient of Piper longum - Akshay Kumar; Tanya Singh Raghuvanshi; Surya Pratap; Horesh Kumar; Bhanu Prakash (Food Chemistry, 2024)

Erratum to: Exploring Dragon Fruit in India: From Taxonomy to Nutritional Benefits and Sustainable Cultivation Practices - Abeer Ali; Akshay Dhillon; Nimisha Sharma; Chandana M.R.; Menaka M.; Pradeep Kumar Vishwakarma; Dhrumeshkumar Chavda (Applied Fruit Science, 2024)

Exploring Dragon Fruit in India: From Taxonomy to Nutritional Benefits and Sustainable Cultivation Practices - Abeer Ali; Akshay Dhillon; Nimisha Sharma; Chandana M.R.; Menaka M.; Pradeep Kumar Vishwakarma; Dhrumeshkumar Chavda (Applied Fruit Science, 2024)

Assessment of Trachyspermum ammi essential oil against Aspergillus flavus, aflatoxin B1 contamination, and post-harvest quality of Sorghum bicolor - Prem Pratap Singh; Atul Kumar Jaiswal; Ritu Singh; Akshay Kumar; Vishal Gupta; Tanya Singh Raghuvanshi; Angad Sharma; Bhanu Prakash (Food Chemistry, 2024)

Key physiological traits for drought tolerance identified through phenotyping a large set of slicing cucumber (Cucumis sativus L.) genotypes under field and water-stress conditions - Anjan Das; A. D. Munshi; Dhandapani Raju; Sudhir Kumar; Dharmendara Singh; Akshay Talukdar; Dhananjay Hongal; Mir Asif Iquebal; Sandeep Kumar; R. C. Bhattacharya; Pragya Ranjan; Oula Ghannoum; et al. (Genetic Resources and Crop Evolution, 2024)

Phytoremediation: An emerging green technology for dissipation of PAHs from soil - Harleen Kaur; Akshay Kumar; Shayla Bindra; Ashish Sharma (Journal of Geochemical Exploration, 2024)

Strength, deformation, and environmental impact assessment of cement stabilized mine overburden soil - Anshumali Mishra; Akshay Dixit; Avinash Kumar Singh; Sarat Kumar Das (Journal of Cleaner Production, 2024)

Evaluating the sensitivity of fine particulate matter (PM2.5) simulations to chemical mechanism in WRF-Chem over Delhi - Rajmal Jat; Chinmay Jena; Prafull P. Yadav; Gaurav Govardhan; Gayatry Kalita; Sreyashi Debnath; Preeti Gunwani; Prodip Acharja; PoojaV. Pawar; Pratul Sharma; Santosh H. Kulkarni; Akshay Kulkarni; et al. (Atmospheric Environment, 2024)

Recent Trends in Nanocarrier-Based Drug Delivery System for Prostate Cancer - Amit Kumar; Akshay Kumar Lunawat; Ashutosh Kumar; Tarun Sharma; Md Moidul Islam; Milan Singh Kahlon; Debanjan Mukherjee; Raj Kumar Narang; Sarjana Raikwar (AAPS PharmSciTech, 2024)

Microplastic pollutants in water: A comprehensive review on their remediation by adsorption using various adsorbents - Akshay Verma; Gaurav Sharma; Amit Kumar; Pooja Dhiman; Genene Tessema Mola; Ali Shan; Chuanling Si (Chemosphere, 2024)

Seafood processing waste as a source of functional components: Extraction and applications for various food and non-food systems - D.S. Akhila; Priyanka Ashwath; Kavitha Guladahalli Manjunatha; Sadanand Dangari Akshay; Vijay Kumar Reddy Surasani; Faisal Rashid Sofi; Kawkabul Saba; Pavan Kumar Dara; Yesim Ozogul; Fatih Ozogul (Trends in Food Science & Technology, 2024)

Comparative analytical analysis and component selection of resistojet thruster for satellite propulsion - Aswin M R; Akshay Pavithran; Yash Mangrole; Shriya Shivaraman; Chinmay Sanjay Kulaye; Amit Kumar Thakur; Balaji R (Journal of Space Safety Engineering, 2024)

A study on speciation and enrichment of rare earth elements (REE) by sequential extraction from a potential coal fly ash resource and its role in REE extractability - Akshay Kumar Singh Choudhary; Santosh Kumar; Sudip Maity (Hydrometallurgy, 2024)

Therapeutic applications of canine platelets and their derivatives: a narrative review - Deeksha Bharti; Y. Ajith; Khan Sharun; S. Amitha Banu; Akshay Kumar; Abhishek Bhardwaj; Shiv Kumar Sidar; Dhaleshwari (Topics in Companion Animal Medicine, 2024)

Finfish fishery of Ashtamudi Estuary, India- A Ramsar site of International significance - Akshay .A. Kumar; Anvar Ali P.H.; Sreekanth Giri Bhavan (Regional Studies in Marine Science, 2023)

Energy, exergy and emission [3E] analysis of Mesua Ferrea seed oil biodiesel fueled diesel engine at variable injection timings - Akshay Jain; Bhaskor Jyoti Bora; Rakesh Kumar; Prabhakar Sharma; Bhaskar Jyoti Medhi; Gottipati Venkata Rambabu; Balakrishnan Deepanraj (Fuel, 2023)

Impact of 280 nm UV-C LEDs on the microbial safety and nutritional quality in tender coconut water - Raj Kumar Maguluri; Akshay H. Dasalkar; Siva Sankara Reddy Singam; Sudheer Kumar Yannam (Food and Humanity, 2023)

Discovery of imidazopyridine-pyrazoline-hybrid structure as SHP-1 agonist that suppresses phospho-STAT3 signaling in human breast cancer cells - Min Hee Yang; Gautam Sethi; Akshay Ravish; Arun Kumar Mohan; Vijay Pandey; Peter E. Lobie; Shreeja Basappa; Basappa Basappa; Kwang Seok Ahn (Chemico-Biological Interactions, 2023)

Recent Advances in Nano-metal Oxide-Biochar Composites for Efficient Removal of Environmental Contaminants - Akshay Kumar Dey; Md. Ahmaruzzaman (Reviews of Environmental Contamination and Toxicology, 2023)

Assessment of morpho-cultural, genetic and pathological diversity of Rhizoctonia solani isolates obtained from different host plants - Asmita Singh; Priya Chandra; Amar Bahadur; Prasenjit Debnath; Gopala Krishnan Subbaiyan; Ranjith K. Ellur; Prashantha Siddappa Tadasanahaller; Akshay Kumar Hosahalli Manjunath; Gaurav Kumar Yadav; Bishnu Maya Bashyal (Journal of Plant Pathology, 2023)

Current scenario and challenges in recycling of human urine generated at source in rail coaches as resource - Kashyap Kumar Dubey; Deepanshi Rajput; Anshu Baldia; Akshay Kumar; Vinod Kumar; Ankush Yadav; Shikha Rao; Yogendra Kumar Mishra (Current Opinion in Green and Sustainable Chemistry, 2023)

Multi-heteroatom doped vehicle exhaust soot derived nano-onion based economical and efficient electrodes for microbial fuel cell: A waste to wealth strategy - Yashmeen Budania; Smriti Mishra; Aradhana Mishra; Animesh Jana; Akshay Modi; Ankit Tyagi; Pradip Kumar; Shiv Singh (Chemical Engineering Journal, 2023)

Salinity and sodicity stresses differentially influence growth and physiology in sapota (Achras zapota L.) - Raj Kumar; Anshuman Singh; Ashwani Kumar; Raj Kumar; Mukesh Kumar Mehla; Akshay Kumar (South African Journal of Botany, 2023)

Applications of autotrophic ammonia oxidizers in bio-geochemical cycles - Deepanshi Rajput; Anshu Baldia; Akshay Kumar; Vinod Kumar; Gunda Mohanakrishna; Kashyap Kumar Dubey (Chemical Engineering Journal, 2023)

Spatially activated conserved auxin-transcription factor regulatory module controls de novo root organogenesis in rice - Tushar Garg; Manoj Yadav; Khrang Khrang Khunggur Mushahary; Akshay Kumar; Vivek Pal; Harshita Singh; Mukesh Jain; Shri Ram Yadav (Planta, 2023)

Pharma 4.0: Use of Advanced Multivariate Analytics at Industrial Scale for Process Troubleshooting, Establishing Material Control and Improving Process Robustness in Pharmaceutical Industrial setting: Case Study - Vaidehi Soman; Akshay Hatewar; Adolf Miranda; Abhaykumar Nalawade; Hansraj Gocher; Ram Kumar (Journal of Pharmaceutical Innovation, 2023)

Assessment of air pollution tolerance and anticipated performance index of roadside trees in urban and semi-urban regions - Akshay Kumar Singh; Sushil Kumar Shukla; Pardeep Singh; Sughosh Madhav; Ashutosh Tripathi (Environmental Monitoring and Assessment, 2023)

Evaluation of uranium content and annual ingestion dose in the surface and ground water bodies of Chittorgarh, Rajasthan, India - Tejpal Menaria; Shailesh Nath Tiwari; Akshay Kumar Patra; Inampudi Vijaya Saradhi; A Vinod Kumar; Rama Kanwar Khangarot; Devendra Singh Rathore (Environmental Monitoring and Assessment, 2023)

A Bacteriophage-Loaded Microparticle Laden Topical Gel for the Treatment of Multidrug-Resistant Biofilm-Mediated Burn Wound Infection - Deepa Dehari; Aiswarya Chaudhuri; Dulla Naveen Kumar; Meraj Anjum; Rajesh Kumar; Akshay Kumar; Dinesh Kumar; Gopal Nath; Ashish Kumar Agrawal (AAPS PharmSciTech, 2023)

A comprehensive record of the fishery resources of a tropical Ramsar wetland: Ashtamudi Estuary, India - Akshay .A. Kumar; Anvar Ali P. H.; Sreekanth Giri Bhavan (Marine Biodiversity, 2023)

Mineralogical variations and geochemical distribution of rare earths and Yttrium (REY) in coal and overburden rocks of some Indian coal mines of Gondwana coalfield - Santosh Kumar; Akshay K Singh Choudhary; A Keshav Krishna; Sudip Maity (Journal of Earth System Science, 2023)

Environmental impacts of air pollution and its abatement by plant species: A comprehensive review - Akshay Kumar Singh; Manoj Kumar; Kuldeep Bauddh; Ajai Singh; Pardeep Singh; Sughosh Madhav; Sushil Kumar Shukla (Environmental Science and Pollution Research, 2023)

Carbon black and chitin nanofibers for green tyres: Preparation and property evaluation - Mariya Mathew; C.D. Midhun Dominic; K.V. Neenu; P.M. Sabura Begum; P. Dileep; T.G. Ajith Kumar; Akshay Alax Sabu; Dhiraj Nagane; Jyotishkumar Parameswaranpillai; Michael Badawi (Carbohydrate Polymers, 2023)

A comparative analysis of the vertical accuracy of multiple open-source digital elevation models for the mountainous terrain of the north-western Himalaya - Parvaiz Ahmad Ganie; Ravindra Posti; Akshay Singh Aswal; Vidya Shree Bharti; Vinay Kumar Sehgal; Debajit Sarma; Pramod Kumar Pandey (Modeling Earth Systems and Environment, 2023)

Dynamic behaviour of integral abutment bridge transition under moving train loads - Akshay Sakhare; Piyush Punetha; Naveen Kumar Meena; Sanjay Nimbalkar; G.-R. Dodagoudar (Transportation Geotechnics, 2023)

Fish assemblage and guild structure in the Ashtamudi Estuary, a tropical Ramsar site in India - Akshay .A. Kumar; Anvar Ali PH; Giri Bhavan Sreekanth (Journal of Environmental Management, 2023)

Application of hybrid Taguchi L16 and desirability for model prediction and optimization in assessment of the performance of a novel Water Hyacinth biodiesel run diesel engine - Akshay Jain; Bhaskor Jyoti Bora; Rakesh Kumar; Prabhakar Sharma; Balakrishnan Deepanraj; Kashif Irshad; Ch. Ravikiran (Fuel, 2023)

Food processing applications of protease activity identified in the methotrexate degrading enzyme of Variovorax paradoxus - Kulkarni Akshay Narayanrao; Venkata Krishna Bayineni; Chandan Kumar Sahu; Ravi-Kumar Kadeppagari (Food and Bioproducts Processing, 2023)

Genetic mapping of some key plant architecture traits in Brassica juncea using a doubled haploid population derived from a cross between two distinct lines: vegetable type Tumida and oleiferous Varuna - Shikha Mathur; Priyansha Singh; Satish Kumar Yadava; Vibha Gupta; Akshay Kumar Pradhan; Deepak Pental (Theoretical and Applied Genetics, 2023)

Foliar zinc fertilization improves yield, biofortification and nutrient-use efficiency of upland rice - Akshay Kumar Yogi; Ram Swaroop Bana; Shanti D. Bamboriya; Ram L. Choudhary; Alison M. Laing; Deepak Singh; Samarth Godara; Subhash Babu; Amresh Chaudhary (Nutrient Cycling in Agroecosystems, 2023)

Differential expression of outer membrane proteins and quinolone resistance determining region mutations can lead to ciprofloxacin resistance in Salmonella Typhi - Sadanand Dangari Akshay; Srajana Nayak; Vijaya Kumar Deekshit; Anusha Rohit; Biswajit Maiti (Archives of Microbiology, 2023)

Solar light–based advanced oxidation processes for degradation of methylene blue dye using novel Zn-modified CeO2@biochar - Akshay Kumar Dey; Soumya Ranjan Mishra; Md. Ahmaruzzaman (Environmental Science and Pollution Research, 2023)

Genetic engineering of plants for phytoremediation: advances and challenges - Kundan Kumar; Akshay Shinde; Varad Aeron; Aanchal Verma; Naseera Sayed Arif (Journal of Plant Biochemistry and Biotechnology, 2023)

Transcription factors controlling the expression of oxidative stress associated genes in rice (Oryza sativa L.) - D. Sujitha; H. G. Jalendra Kumar; Garima Thapliayal; Garima Pal; P. A. Vanitha; Akshay Uttarkar; Mahesh Patil; B. H. Rajashekar Reddy; Vidya Niranjan; Usha Rayalcheruvu; Geetha Govind; M. Udayakumar; et al. (Plant Biotechnology Reports, 2023)

Multiomics and optobiotechnological approaches for the development of microalgal strain for production of aviation biofuel and biorefinery - Akshay Kumar; Anshu Baldia; Deepanshi Rajput; Suneel Kateriya; Vikash Babu; Kashyap Kumar Dubey (Bioresource Technology, 2023)

Prediction of meteorological drought and standardized precipitation index based on the random forest (RF), random tree (RT), and Gaussian process regression (GPR) models - Ahmed Elbeltagi; Chaitanya B. Pande; Manish Kumar; Abebe Debele Tolche; Sudhir Kumar Singh; Akshay Kumar; Dinesh Kumar Vishwakarma (Environmental Science and Pollution Research, 2023)

Engineering microalgae as the next-generation food - Anshu Baldia; Deepanshi Rajput; Akshay Kumar; Ashok Pandey; Kashyap Kumar Dubey (Systems Microbiology and Biomanufacturing, 2023)

Effect of sub-minimum inhibitory concentration of ceftriaxone on the expression of outer membrane proteins in Salmonella enterica serovar Typhi - Sadanand Dangari Akshay; Karanth Padyana Anupama; Vijaya Kumar Deekshit; Anusha Rohit; Biswajit Maiti (World Journal of Microbiology and Biotechnology, 2022)

Correction to: Spatio-temporal variability and trend analysis of rainfall in Wainganga river basin, Central India, and forecasting using state-space models - Nanabhau S. Kudnar; Pranaya Diwate; Varun Narayan Mishra; Prashant K. Srivastava; Akshay Kumar; Manish Pandey (Theoretical and Applied Climatology, 2022)

Spatio-temporal variability and trend analysis of rainfall in Wainganga river basin, Central India, and forecasting using state-space models - Nanabhau S. Kudnar; Pranaya Diwate; Varun Narayan Mishra; Prashant K. Srivastava; Akshay Kumar; Manish Pandey (Theoretical and Applied Climatology, 2022)

Toxicity, Environmental Monitoring and Removal Strategies of Arsenic - Akshay Pawar; Simranjeet Singh; Praveen Chandra Ramamurthy; Amith G. Anil; Nabila Shehata; Daljeet Singh Dhanjal; Tandreborekaval Swamy Sunil Kumar Naik; Parul Parihar; Ram Prasad; Joginder Singh (International Journal of Environmental Research, 2022)

Assessment of groundwater quality and human health risks from fluoride in Lower Satluj Basin, Punjab, India - Akshay Kumar Chaudhry; Payal Sachdeva (Arabian Journal of Geosciences, 2022)

A systematic basin-wide approach for locating and assessing volumetric potential of rainwater harvesting sites in the urban area - Deshbhushan Patil; Gaurav Kumar; Akshay Kumar; Rajiv Gupta (Environmental Science and Pollution Research, 2022)

Glyphosate-resistant Brassica juncea (oilseed mustard) transgenics for possible control of root parasite Orobanche aegyptiaca and conservation agriculture - Parul Agarwal; Arundhati Mukhopadhyay; Vibha Gupta; Akshay Kumar Pradhan; Deepak Pental (Journal of Plant Biochemistry and Biotechnology, 2022)

A review on mineralogical speciation, global occurrence and distribution of rare earths and Yttrium (REY) in coal ash - Akshay K Singh Choudhary; Santosh Kumar; Sudip Maity (Journal of Earth System Science, 2022)

Assessment of Role and Efficacy of Curcumin and Quercetin in Preventing Lead-Induced Oxidative Stress in Rats - Mohd Zahid; Pushkar Singh Rawat; Shalini Singh; Akshay Kumar Gupta; Rumana Ahmad; Abbas Ali Mahdi; Md. Kaleem Ahmad; Sudhir Mehrotra (Indian Journal of Clinical Biochemistry, 2022)

Association mapping, trait variation, interaction and population structure analysis in cucumber (Cucumis sativus L.) - Rahul Kumar; Anilabh Das Munshi; Tusar Kanti Behera; Gograj Singh Jat; Harshawardhan Choudhary; Akshay Talukdar; Prasanta Dash; Deepak Singh (Genetic Resources and Crop Evolution, 2022)

Botanicals for Sustainable Management of Stored Food Grains: Pesticidal Efficacy, Mode of Action and Ecological Risk Assessment Using Computational Approaches - Bhanu Prakash; Prem Pratap Singh; Akshay Kumar; Vishal Gupta (Anthropocene Science, 2022)

Population structure, gene flow and genetic diversity analyses based on agro-morphological traits and microsatellite markers within cultivated and wild germplasms of okra [Abelmoschus esculentus (L.) Moench.] - Anjan Das; Ramesh Kumar Yadav; Harshwardhan Choudhary; Suman Lata; Saurabh Singh; Chavlesh Kumar; Shilpi Kumari; G. Boopalakrishnan; Rakesh Bhardwaj; Akshay Talukdar (Genetic Resources and Crop Evolution, 2022)

Quercetin Mitigates Red Blood Cell Membrane Bound Na+, K+-ATPase Transporter During Human Aging - Akshay Kumar; Pawan Kumar Maurya (The Journal of Membrane Biology, 2021)

Monsoonal rainfall induced shallow earthquake Swarm in the Amravati district of the central India - Monika Wadhawan; Naresh Rana; Vineet Gahalaut; Manjeet Singh; Kulbir Singh; G Suresh; O P Mishra; Akshay Kumar Joshi; A V Kulkarni; Mahendra Singh; A K Das (Journal of Earth System Science, 2021)

Infected insect gut reveals differentially expressed proteins for cellular redox, metal resistance and secretion system in Yersinia enterocolitica-Helicoverpa armigera pathogenic model - Shruti Ahlawat; Amarjeet Kumar Singh; Akshay Shankar; Asha Yadav; Krishna Kant Sharma (Biotechnology Letters, 2021)

Electrochemical Probing of H2O2 Using TiO2-ZrO2-HfO2 Modified Glassy Carbon Electrode: A Promoted Sacrificial Behavior of Hf4+ ions - Akshay Krishnakumar; Parthasarathy Srinivasan; Ganesh Kumar Mani; Rio Kita; Kunio Okimura; John Bosco Balaguru Rayappan; Kazuyoshi Tsuchiya (Water, Air, & Soil Pollution, 2021)

Assessment of WRF-CHEM Simulated Dust Using Reanalysis, Satellite Data and Ground-Based Observations - Akshay Rajeev; Charu Singh; Sanjeev Kumar Singh; Prakash Chauhan (Journal of the Indian Society of Remote Sensing, 2021)

Fusarium head blight of wheat in India‐variability in pathogens associated and sources of resistance: an overview - Mahender Singh Saharan; H. M. Akshay Kumar; Malkhan Singh Gurjar; Rashmi Aggarwal (Indian Phytopathology, 2021)

Statistical interpretation of environmental influencing parameters on COVID-19 during the lockdown in Delhi, India - Amit Awasthi; Aditi Sharma; Prabhjot Kaur; Balakrishnaiah Gugamsetty; Akshay Kumar (Environment, Development and Sustainability, 2021)

Groundwater quality assessment using geospatial technique based water quality index (WQI) approach in a coal mining region of India - Akshay Kumar; Akhouri Pramod Krishna (Arabian Journal of Geosciences, 2021)

Determination of sensitivity of drainage morphometry towards hydrological response interactions for various datasets - Akshay Omprakash Jain; Tejaskumar Prakashchandra Thaker; Anil Kumar Misra; Anupam Kumar Singh; Priyanka Kumari (Environment, Development and Sustainability, 2021)

Damage Characteristics of Jalore Granitic Rocks After Thermal Cycling Effect for Nuclear Waste Repository - P. K. Gautam; R. Dwivedi; Akshay Kumar; Anil Kumar; A. K. Verma; K. H. Singh; T. N. Singh (Rock Mechanics and Rock Engineering, 2021)

Elucidation of antifungal toxicity of Callistemon lanceolatus essential oil encapsulated in chitosan nanogel against Aspergillus flavus using biochemical and in-silico approaches - Prem Pratap Singh; Akshay Kumar; Bhanu Prakash (Food Additives & Contaminants: Part A, 2020)

Discovery and Utilization of EST-SSR Marker Resource for Genetic Diversity and Population Structure Analyses of a Subtropical Bamboo, Dendrocalamus hamiltonii - Abhishek Bhandawat; Vikas Sharma; Pradeep Singh; Romit Seth; Akshay Nag; Jagdeep Kaur; Ram Kumar Sharma (Biochemical Genetics, 2019)

BjuWRR1, a CC-NB-LRR gene identified in Brassica juncea, confers resistance to white rust caused by Albugo candida - Heena Arora; K. Lakshmi Padmaja; Kumar Paritosh; Nitika Mukhi; A. K. Tewari; Arundhati Mukhopadhyay; Vibha Gupta; Akshay K. Pradhan; Deepak Pental (Theoretical and Applied Genetics, 2019)

Nanoencapsulated methyl salicylate as a biorational alternative of synthetic antifungal and aflatoxin B1 suppressive agents - Anupam Kujur; Amrita Yadav; Akshay Kumar; Prem Pratap Singh; Bhanu Prakash (Environmental Science and Pollution Research, 2019)

Scale Minimization in Sugar Industry Evaporators using Nanoporous Industrial Bio-solid Waste Bagasse Fly Ash - Rajeev Nath Tiwari; Choudhary Akshay Gandharv; Keya Dharamvir; Suresh Kumar; Gaurav Verma (Sugar Tech, 2019)

NO protect the wheat embryo from oxidative damage by triggering the biochemical defence network and amylolytic activity - Ranjeet R. Kumar; Mohd. Tasleem; Khushboo Singh; Sumedha Ahuja; Akshay Sakhare; Sudhir Kumar; Suneha Goswami; Sivdhar Singh; Gyanendra P. Singh; Viswanathan Chinnusamy; Shelly Praveen (Plant Physiology Reports, 2019)

Pretreated animal and human waste as a substantial nutrient source for cultivation of microalgae for biodiesel production - Vinod Kumar; Akshay Kumar; Manisha Nanda (Environmental Science and Pollution Research, 2018)

What signals do herbivore-induced plant volatiles provide conspecific herbivores? - Subhash Shivaramu; Pagadala Damodaram Kamala Jayanthi; Vivek Kempraj; Raghavendra Anjinappa; Bakthavatsalam Nandagopal; Akshay Kumar Chakravarty (Arthropod-Plant Interactions, 2017)

Exploring the heat-responsive chaperones and microsatellite markers associated with terminal heat stress tolerance in developing wheat - Ranjeet R. Kumar; Suneha Goswami; Mohammad Shamim; Kavita Dubey; Khushboo Singh; Shweta Singh; Yugal K. Kala; Ravi R.K. Niraj; Akshay Sakhrey; Gyanendra P. Singh; Monendra Grover; Bhupinder Singh; et al. (Functional & Integrative Genomics, 2017)

Nanoscale wide-band semiconductors for photocatalytic remediation of aquatic pollution - Biplab Sarkar; Akshay Vishnu Daware; Priya Gupta; Kishore Kumar Krishnani; Sunandan Baruah; Surajit Bhattacharjee (Environmental Science and Pollution Research, 2017)

Identification of genic SSRs and construction of a SSR-based linkage map in Brassica juncea - Namrata Dhaka; Arundhati Mukhopadhyay; Kumar Paritosh; Vibha Gupta; Deepak Pental; Akshay K. Pradhan (Euphytica, 2017)

Identification and characterization of novel UniGene-derived microsatellite markers in Podophyllum hexandrum (Berberidaceae) - AKSHAY NAG; PANKAJ BHARDWAJ; PARAMVIR SINGH AHUJA; RAM KUMAR SHARMA (Journal of Genetics, 2016)

First report of association of potato virus X and potato virus Y and ‘Candidatus Phytoplasma trifolii’ in brinjal in India - Manish Kumar; Akshay Katiyar; Madhupriya; G. P. Rao (VirusDisease, 2016)

Assessment of genetic diversity of Saltol QTL among the rice (Oryza sativa L.) genotypes - Showkat Ahmad Ganie; Mrinmoi Jyoti Borgohain; Kashyap Kritika; Akshay Talukdar; Dipti Ranjan Pani; Tapan Kumar Mondal (Physiology and Molecular Biology of Plants, 2016)

Novel microsatellite markers identification and diversity characterization in Pteris cretica L. - Vishal Kumar; Abhishek Bhandawat; Himanshu Sharma; Akshay Nag; Ram Kumar Sharma (Journal of Plant Biochemistry and Biotechnology, 2016)

Genetic diversity and population structure of endangered Aquilaria malaccensis revealed potential for future conservation - PRADEEP SINGH; AKSHAY NAG; RAJNI PARMAR; SNEHA GHOSH; BRIJMOHAN SINGH BHAU; RAM KUMAR SHARMA (Journal of Genetics, 2015)

Functionally relevant novel microsatellite markers for efficient genotyping in Stevia rebaudiana Bertoni - ABHISHEK BHANDAWAT; HIMANSHU SHARMA; AKSHAY NAG; SANATSUJAT SINGH; PARAMVIR SINGH AHUJA; RAM KUMAR SHARMA (Journal of Genetics, 2015)

Geospatial and hydrological modeling to assess hydropower potential zones and site location over rainfall dependent Inland catchment - Manish Kumar Goyal; Vishal Singh; Akshay H. Meena (Water Resources Management, 2015)

Development and characterization of polymorphic microsatellites markers in endangered Aquilaria malaccensis - Pradeep Singh; Himanshu Sharma; Akshay Nag; Brijmohan Singh Bhau; Ram Kumar Sharma (Conservation Genetics Resources, 2015)

Mapping of yellow mosaic virus (YMV) resistance in soybean (Glycine max L. Merr.) through association mapping approach - Bhupender Kumar; Akshay Talukdar; Khushbu Verma; Indu Bala; G. D. Harish; Sarmrat Gowda; S. K. Lal; R. L. Sapra; K. P. Singh (Genetica, 2015)

Population structure and association mapping studies for important agronomic traits in soybean - BHUPENDER KUMAR; AKSHAY TALUKDAR; INDU BALA; KHUSHBU VERMA; SANJAY KUMAR LAL; RAMESH LAL SAPRA; B. NAMITA; SUBHASH CHANDER; RESHU TIWARI (Journal of Genetics, 2014)

Tetralocular ovary and high silique width in yellow sarson lines of Brassica rapa (subspecies trilocularis) are due to a mutation in Bra034340 gene, a homologue of CLAVATA3 in Arabidopsis - Satish Kumar Yadava; Kumar Paritosh; Priya Panjabi-Massand; Vibha Gupta; Atika Chandra; Y. S. Sodhi; Akshay K. Pradhan; Deepak Pental (Theoretical and Applied Genetics, 2014)

Does toll-like receptor-3 (TLR-3) have any role in Indian AMD phenotype? - Neel Kamal Sharma; Kaushal Sharma; Amod Gupta; Sudesh Prabhakar; Ramandeep Singh; Pawan Kumar Gupta; Akshay Anand (Molecular and Cellular Biochemistry, 2014)

AFLP and RAPD based genetic diversity assessment of industrially important reed bamboo (Ochlandra travancorica Benth) - Akshay Nag; Priyanka Gupta; Vikas Sharma; Anil Sood; Paramvir Singh Ahuja; Ram Kumar Sharma (Journal of Plant Biochemistry and Biotechnology, 2013)

QTL mapping of yield-associated traits in Brassica juncea: meta-analysis and epistatic interactions using two different crosses between east European and Indian gene pool lines - Satish Kumar Yadava; N. Arumugam; Arundhati Mukhopadhyay; Yashpal Singh Sodhi; Vibha Gupta; Deepak Pental; Akshay K. Pradhan (Theoretical and Applied Genetics, 2012)

Genetic Structure of Indian Valerian (Valeriana jatamansi) Populations in Western Himalaya Revealed by AFLP - Subramani Rajkumar; Sunil Kumar Singh; Akshay Nag; Paramvir S. Ahuja (Biochemical Genetics, 2011)

Eliminating expression of erucic acid-encoding loci allows the identification of “hidden” QTL contributing to oil quality fractions and oil content in Brassica juncea (Indian mustard) - Arun Jagannath; Yashpal Singh Sodhi; Vibha Gupta; Arundhati Mukhopadhyay; Neelakantan Arumugam; Indira Singh; Soma Rohatgi; Pradeep Kumar Burma; Akshay Kumar Pradhan; Deepak Pental (Theoretical and Applied Genetics, 2011)

Molecular mapping reveals two independent loci conferring resistance to Albugo candida in the east European germplasm of oilseed mustard Brassica juncea - Priya Panjabi-Massand; Satish Kumar Yadava; Pankaj Sharma; Arvinder Kaur; Amarendra Kumar; N. Arumugam; Yashpal Singh Sodhi; Arundhati Mukhopadhyay; Vibha Gupta; Akshay K. Pradhan; Deepak Pental (Theoretical and Applied Genetics, 2010)

Bacopa monniera exerts antiamnesic effect on diazepam-induced anterograde amnesia in mice - Sudesh Prabhakar; Manish Kumar Saraf; Promila Pandhi; Akshay Anand (Psychopharmacology, 2008)

A passage through in vitro culture leads to efficient production of marker-free transgenic plants in Brassica juncea using the Cre–loxP system - N. Arumugam; Vibha Gupta; Arun Jagannath; Arundhati Mukhopadhyay; Akshay K. Pradhan; Pradeep Kumar Burma; Deepak Pental (Transgenic Research, 2007)

Forecasting shield pressures at a longwall face using artificial neural networks - Debasis Deb; Akshay Kumar; Rajat Pal Singh Rosha (Geotechnical and Geological Engineering, 2006)